Protective role of IL33 signaling in negative pregnancy outcomes associated with lipopolysaccharide exposure. Issue 2 (10th January 2021) - Kozai, Keisuke; Iqbal, Khursheed; Moreno‐Irusta, Ayelen; Scott, Regan L.; Simon, Mikaela E.; Dhakal, Pramod; Fields, Patrick E.; Soares, Michael J.
Abstract: Interleukin 33 (IL33) signaling has been implicated in the establishment and maintenance of pregnancy and in pregnancy disorders. The goal of this project was to evaluate the role of IL33 signaling in rat pregnancy. The rat possesses hemochorial placentation with deep intrauterine trophoblast invasion; features also characteristic of human placentation. We generated and characterized a germline mutant rat model for IL33 using CRISPR/Cas9 genome editing. IL33 deficient rats exhibited deficits in lung responses to an inflammatory stimulus (Sephadex G‐200) and to estrogen‐induced uterine eosinophilia. Female rats deficient in IL33 were fertile and exhibited pregnancy outcomes (gestation length and litter size) similar to wild‐type rats. Placental weight was adversely affected by the disruption of IL33 signaling. A difference in pregnancy‐dependent adaptations to lipopolysaccharide (LPS) exposure was observed between wild‐type and IL33 deficient pregnancies. Pregnancy in wild‐type rats treated with LPS did not differ significantly from pregnancy in vehicle‐treated wild‐type rats. In contrast, LPS treatment decreased fetal survival rate, fetal and placental weights, and increased fetal growth restriction in IL33 deficient rats. In summary, a new rat model for investigating IL33 signaling has been established. IL33 signaling participates in the regulation of placental development and protection against LPS‐induced fetal and placental growth restriction.